2023
DOI: 10.1161/circulationaha.122.061130
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I–Interacting Kinase Affects Cardiomyocyte S-Phase Activity but Not Cardiomyocyte Proliferation

Abstract: Background: Identifying genetic variants which impact the level of cell cycle reentry and establishing the degree of cell cycle progression in those variants could help guide development of therapeutic interventions aimed at effecting cardiac regeneration. We observed that C57Bl6/NCR (B6N) mice have a marked increase in cardiomyocyte S-phase activity following permanent coronary artery ligation as compared to infarcted DBA/2J (D2J) mice. Methods: Cardiomyocyte cell cycle activity post-infarction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…11 They noted a similar increase in HW/ BW, but only a nonsignificant trend toward increase in cardiomyocyte size. Noteworthy is the reported 10% EdU labeling rate of cardiomyocytes, magnitudes higher 9 It is difficult to explain and points to methodological problems.…”
Section: Eschenhagenmentioning
confidence: 99%
See 2 more Smart Citations
“…11 They noted a similar increase in HW/ BW, but only a nonsignificant trend toward increase in cardiomyocyte size. Noteworthy is the reported 10% EdU labeling rate of cardiomyocytes, magnitudes higher 9 It is difficult to explain and points to methodological problems.…”
Section: Eschenhagenmentioning
confidence: 99%
“…The Field group reported a BrdU/EdU labeling index in mice (over 14 days) of 0.6% and calculated that such rate would replace 50% of the heart´s cardiomyocyte over 569 days. 9 Obviously, 0.1% renewal in 28 days would need years to account for a doubling of cardiomyocyte numbers. One could argue that Nakada et al employed low doses of oral BrdU that underestimated the true DNA synthesis rate.…”
Section: Eschenhagenmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, TNNI3K might be involved in the regulation of metabolic processes and oxidative stress. Reuter et al 8 speculated that increased levels of oxidative stress render TNNI3K-expressing cardiomyocytes more permissive to cell-cycle reentry. However, it has been reported that enhanced DNA damage attributable to increased reactive oxygen species production prevents DNA replication, resulting in cell-cycle arrest.…”
mentioning
confidence: 99%
“…In this issue of Circulation , Reuter et al 8 and Yu et al 9 addressed these questions by studying cardiac troponin I–interacting kinase (TNNI3K)–dependent S-phase activity and E2 promoter binding factor (E2F) 7 and 8–dependent polyploidization of cardiomyocytes, respectively (Figure). Reuter et al observed pronounced differences in cardiomyocyte S-phase activity after permanent coronary artery ligation in mice of different genetic backgrounds.…”
mentioning
confidence: 99%